Giant Congenital Blue Nevus Presenting as Cutis Verticis Gyrata: A Case Report and Review of the Literature. (December 2021) - Cullom, Melissa E.; Fraga, Garth R.; Reeves, Alan R.; Bhavsar, Dhaval; Andrews, Brian T.
Objectives: Cerebriform intradermal nevus and giant congenital blue nevi are rarely reported melanocytic nevi with clinical and histopathologic similarities. Both are known to produce cutis verticis gyrata. We report a significantly large occipital scalp congenital blue nevus with secondary cutis verticis gyrata. The aim of this report is to increase clinical awareness of this entity, highlight histopathologic and mutational features of cerebriform intradermal nevi and giant congenital blue nevi, and stress the importance of clinicopathologic correlation for diagnosis. Methods: Case report and review of the literature. Results: A 20-year-old Asian male presented with a long-standing, large (20 cm × 30 cm), exophytic tumor at the occipital scalp and posterior neck. The skin overlying the lesion was arranged in thick folds resembling the surface of the brain, devoid of hair follicles, and discolored by salt-and-pepper pattern hyperpigmentation. After correlating the clinical and histopathologic findings, we diagnosed giant congenital blue nevus with secondary cutis verticis gyrata. Staged surgical excision was performed with subsequent treatment for hypertrophic scarring and occipital alopecia. Conclusions: Cerebriform intradermal nevus and giant congenital blue nevus have overlapping histologic and clinical features. Head and neck surgeons should be aware that nomenclature of these tumors is subjective and often imprecise. Diagnosis requires correlation of clinical findings, patient history, and histopathology. Surgical excision is advised due to rare malignant transformation potential.